Youth Interfaith Dialogue in Everyday Citizenship in Indonesia: Bridging Religious Diversity and Citizenship Challenges - Kusmayani, Anisa Eka Putri (Parahyangan Catholic University, 2023)
This research explores the role of interfaith dialogue among Indonesian youth in fostering everyday citizenship, particularly within the context of religious diversity. The study draws on the dynamics of interfaith engagement, emphasizing its significance in promoting social cohesion, peace, and civic participation. The framework integrates the